NTU Singapore and SMU launch PhD exchange programme - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
From January next year, PhD students from Nanyang Technological University, Singapore (NTU Singapore) and the Singapore Management University (SMU) will be able to enrol for postgraduate courses in both universities. Under the new NTU-SMU PhD Student Exchange Programme, eligible PhD students from NTU Singapore and SMU can attend classes at the other university, the first such graduate academic programme tie-up between the two universities. The programme combines the unique strengths of both young universities, allowing students from both universities to benefit from the wide-ranging PhD course offerings.